Detection of organic dyes by surface-enhanced Raman spectroscopy using plasmonic NiAg nanocavity films - Petruš, Ondrej; Macko, Ján; Oriňaková, Renáta; Oriňak, Andrej; Múdra, Erika; Kupková, Miriam; Farka, Zdeněk; Pastucha, Matěj; Socha, Vladimír (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2021)
This work presents the NiAg nanocavity film for the detection of organic dyes by surface-enhanced Raman spectroscopy (SERS). Nanocavity films were prepared by colloidal lithography using 518-nm polystyrene spheres combined with the electrochemical deposition of Ni supporting layer and Ag nanoparticles homogeneous SERS-active layer. The theoretical study was modelled by finite-difference time-domain (FDTD) simulation of electromagnetic field enhancement near the nanostructured surface and experimentally proven by SERS measurement of selected organic dyes (rhodamine 6G, crystal violet, methylene blue, and malachite green oxalate) in micromolar concentration. Furthermore, the concentration dependence was investigated to prove the suitability of NiAg nanocavity films to detect ultra-low concentrations of samples. The detection limit was 1.3 × 10-12, 1.5 × 10-10, 1.4 × 10-10, 7.5 × 10-11 mol·dm-3, and the standard deviation was 20.1%, 13.8%, 16.7%, and 19.3% for R6G, CV, MB, and MGO, respectively. The analytical enhancement factor was 3.4 × 105 using R6G as a probe molecule. The principal component analysis (PCA) was performed to extract the differences in complex spectra of the dyes where the first and second PCs carry 42.43% and 31.39% of the sample variation, respectively. The achieved results demonstrated the suitability of AgNi nanocavity films for the SERS-based detection of organic dyes, with a potential in other sensing applications.
Keywords: Colloidal litography; PCA analysis; SERS; FDTD